MEASURING THE EFFECT OF EMPLOYEE CLASS DISTINCTION AND ACCREDITATION RANK ON THE DESIRE TO CONTINUE STUDYING FOR MASTER OF MANAGEMENT STUDENTS IN YOGYAKARTA - Akhmad , Jazuli; Purwanto, Wahyu (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
The decline in accreditation ranking 43 students or 62.3% still want to continue their studies while 26 students or 37.7% want to postpone continuing their studies. The p-value of significance in the Variables in the Equation table of the class group variable is 0.051> 0.05, meaning that partially the class group has no effect on the desire to continue their studies, as well as for the accreditation variable, significant at p-value 0.569> 0.05, meaning that the accreditation rating has no effect on students' desire to continue their studies.